A surface enhanced Raman spectroscopic study of interactions between casein and polymethoxyflavones. (14th December 2012) - He, Lili; Zheng, Jinkai; Labuza, Theodore P.; Xiao, Hang
<x xml:space="preserve">Abstract</x> Molecular interactions between dietary flavonoids and other food components play important roles in the biological fate and activities of flavonoids. Herein, surface‐enhanced Raman spectroscopy (SERS) was used to study the molecular interactions between casein, a major milk protein, and three structurally closely related polymethoxyflavones (PMFs), nobiletin, 5, 3′, 4′‐tridemethylnobiletin, and 3′, 4′‐didemethylnobiletin. SERS was conducted after either conjugating casein onto silver (Ag) dendrites to interact with PMFs, or conjugating PMFs onto Ag to interact with casein. Our results show distinct selectivity of PMFs in binding to Ag dendrites and casein. Hydroxyl groups on PMFs played a key role in the interactions between PMFs and casein and Ag. Methylation reaction at certain positions of PMF structures reduced the binding capacity of PMFs to both casein and Ag. This rapid and simple method can be extended to study the interactions between other flavonoids and various food components, especially useful when there are a large number of samples. Copyright © 2012 John Wiley & Sons, Ltd.